Spindle pole body component 24 homolog potentiates tumor progression via regulation of SRY‐box transcription factor 2 in clear cell renal cell carcinoma. Issue 2 (14th January 2022) - Sun, Chengfang; Wei, Jingchao; Long, Zhilin; Zhao, Weixi; Huangfu, Qi; Xie, Qi; Wang, Bohan; Wen, Jiaming
Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common pathological subtype of human kidney cancer with a high probability of metastasis. To understand the molecular processing essential for ccRCC tumorigenicity, we conducted an integrative in silico analysis of The Cancer Genome Atlas (TCGA) ccRCC dataset and clustered randomly interspersed short palindromic repeats (CRISPR) screening dataset of ccRCC cell lines from Depmap. We identified spindle pole body component 24 homolog (SPC24) as an essential gene for ccRCC cell lines with prognostic significance in the TCGA database. Targeting SPC24 by CRISPR/Cas9‐mediated gene knockout attenuated ccRCC proliferation, metastasis, and in vivo tumor growth. Furthermore, we found that SPC24 regulates metastasis genes expression in a SRY‐box transcription factor 2 (SOX2)‐dependent manner. The anti‐proliferative effects of SPC24 knockout were strengthened with SOX2 knockdown. Collectively, our findings suggest SPC24 has a pivotal function in promoting ccRCC progression, providing a new insight for the treatment of ccRCC.